PENYELESAIAN PENGADUAN MALADMINISTRASI OLEH OMBUDSMAN PERWAKILAN PROVINSI RIAU - Afriliza Afriliza; Dessy Artina; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The higher the quality of services provided to consumers, the more likely the agency will develop, and vice versa if the agency provides unsatisfactory services to the community, it is likely that the agency will be slow to develop. In fact, the products of government organizations are services to the community. People long for good and fast public services with a balance between the power they have and the responsibilities that must be given to the people they serve. This thesis discusses the settlement of maladministration complaints by the Ombudsman Representative of Riau Province.The type of research is juridical sociological or field research, namely examining the applicable legal provisions and what is happening in reality in society. The research location is in the Office of the Ombudsman Representative in Riau. Sources of data are: primary data and secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques in this study were interviews and literature review. Data analysis was carried out qualitatively, namely the data obtained not using statistics or mathematics or the like.The conclusion of this study is the inhibiting factors in carrying out the duties of the Ombudsman of the Republic of Indonesia Representative of the Riau Province, namely the first legal factor, the second the limited budget, the third factor of inadequate facilities and facilities and the fourth the lack of existence of the Ombudsman of the Republic of Indonesia Representative of the Riau Province. Efforts to overcome the obstacles that exist in the Ombudsman of the Republic of Indonesia Representative of the Province of Riau are by improving the law, increasing the budget for the Ombudsman of the Republic of Indonesia Representative of the Province of Riau, increasing the number of membership personnel of the Ombudsman of the Republic of Indonesia Representative of the Province of Riau, improving office facilities supporting the performance of the Ombudsman of the Republic of Indonesia. Indonesia Representative of Riau Province and the need for outreach to the public regarding the existence of the Ombudsman of the Republic of Indonesia Representative of Riau Province. The author's suggestion to the Ombudsman of the Republic of Indonesia is to further improve performance both in terms of completing reports and preventing maladministration. Ombudsman Representative of Riau Province to the public who are in direct contact with the administration. In addition, to strengthen its existence for the existence of the Ombudsman Republic of Indonesia Representative of Riau Province so that it is known by the public, especially people outside the Pekanbaru area.Keywords: Complaint Resolution - Maladministration - Ombudsman Representative of Riau Province